Relationship Between Job Satisfaction and Performance: Conceptual Approach - Evi Fitrotun Najiah; Mugi Harsono (Jurnal Mantik, 2021)
In writing this article aims to explain the related conceptual framework that describes the relationship of job satisfaction variables with performance. Several theoretical concepts from the factors that form job satisfaction, performance to the conceptual framework are discussed in this article. The final goal of this study is to observe the relationship between job satisfaction and performance variables, which is very important in the development of further research related to the relationship between job satisfaction and performance.